2020
DOI: 10.1002/jbmr.4313
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts Generate Testosterone From DHEA and Activate Androgen Signaling in Prostate Cancer Cells

Abstract: Bone metastasis is a complication of prostate cancer in up to 90% of men afflicted with advanced disease. Therapies that reduce androgen exposure remain at the forefront of treatment. However, most prostate cancers transition to a state whereby reducing testicular androgen action becomes ineffective. A common mechanism of this transition is intratumoral production of testosterone (T) using the adrenal androgen precursor dehydroepiandrosterone (DHEA) through enzymatic conversion by 3β‐ and 17β‐hydroxysteroid de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Most mCRPC remains androgen‐dependent via various mechanisms that increase AR signaling despite castrate levels of circulating testosterone following ADT 59 . One such mechanism is tumoral uptake and intracellular conversion of adrenal androgens 60 . The adrenal gland itself is a unique environment due to the local secretion of adrenal androgens by the zona reticularis of the adrenal cortex which are not subject to decreased adrenal androgens following castration, making it a more hospitable environment for tumor colonization 61 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most mCRPC remains androgen‐dependent via various mechanisms that increase AR signaling despite castrate levels of circulating testosterone following ADT 59 . One such mechanism is tumoral uptake and intracellular conversion of adrenal androgens 60 . The adrenal gland itself is a unique environment due to the local secretion of adrenal androgens by the zona reticularis of the adrenal cortex which are not subject to decreased adrenal androgens following castration, making it a more hospitable environment for tumor colonization 61 .…”
Section: Discussionmentioning
confidence: 99%
“…59 One such mechanism is tumoral uptake and intracellular conversion of adrenal androgens. 60 The adrenal gland itself is a unique environment due to the local secretion of adrenal androgens by the zona reticularis of the adrenal cortex which are not subject to decreased adrenal androgens following castration, making it a more hospitable environment for tumor colonization. 61 Similarly, tumor DHEA and androstenedione have been shown to be within or above the normal limits in the adrenal glands of CRPC patients receiving ADT.…”
Section: Castration Leads To An Upregulation Of Ar and Ar-v7 In Pdm 167mentioning
confidence: 99%
“…Recent evidence indicated that osteoblasts not only respond to steroid hormones but can also synthetize testosterone from DHEA under pathological conditions during the development of prostate cancer bone metastases [106]. Intratumoral production of the adrenal androgen precursor DHEA allowed bone-forming osteoblasts to convert and secrete androgens to drive the development of osteosclerotic skeletal lesions [106]. Both human and murine osteoblasts were found to express Hsd3b2 and Cyp17a1 enzymes, suggesting that osteoblasts are capable of generating testosterone from DHEA [106].…”
Section: Role Of Extraglandular Steroidogenesis In the Bone Microenvi...mentioning
confidence: 99%
“…Intratumoral production of the adrenal androgen precursor DHEA allowed bone-forming osteoblasts to convert and secrete androgens to drive the development of osteosclerotic skeletal lesions [106]. Both human and murine osteoblasts were found to express Hsd3b2 and Cyp17a1 enzymes, suggesting that osteoblasts are capable of generating testosterone from DHEA [106]. In another publication authors also suggested a role for osteoblasts in promoting castration-resistant prostate cancer development by altering intratumoral steroidogenesis [107].…”
Section: Role Of Extraglandular Steroidogenesis In the Bone Microenvi...mentioning
confidence: 99%
See 1 more Smart Citation